Green consumerism an A-to-Z guide - Mansvelt, Juliana (Thousand Oaks, Calif. SAGE, 2010)
This title covers the consumption, availability, and distribution of energy and other resources in the personal consumer environment.
"SAGE reference online."
Title from home page (viewed Jan. 24, 2011).
Mode of access: World Wide Web.
System requirements: Internet Explorer 6.0 (or higher) Firefox 2.0 (or higher).
Available as searchable text in HTML format.
Keywords: Consumption (Economics) -- Environmental aspects; Environmental responsibility; Green products; Electronic books